2017
DOI: 10.1212/wnl.0000000000003819
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in noncoding regions of GJB1 are a major cause of X-linked CMT

Abstract: Objective:To determine the prevalence and clinical and genetic characteristics of patients with X-linked Charcot-Marie-Tooth disease (CMT) due to mutations in noncoding regions of the gap junction β-1 gene (GJB1).Methods:Mutations were identified by bidirectional Sanger sequence analysis of the 595 bases of the upstream promoter region, and 25 bases of the 3′ untranslated region (UTR) sequence in patients in whom mutations in the coding region had been excluded. Clinical and neurophysiologic data were retrospe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
53
0
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 58 publications
(63 citation statements)
references
References 22 publications
3
53
0
7
Order By: Relevance
“…The majority of mutations in GJB1 are missense but rare ones have been described in the 5′ UTR . Recently, a GJB1 mutation (c.*15C>T) in the 3′ UTR was reported in 2 nuclear families each with only a single affected male, precluding proof of cosegregation with disease . The present study has documented cosegregation of the c.*15C>T GJB1 mutation in 4 branches of a large family, with confirmation by linkage analysis.…”
Section: Discussionsupporting
confidence: 51%
See 2 more Smart Citations
“…The majority of mutations in GJB1 are missense but rare ones have been described in the 5′ UTR . Recently, a GJB1 mutation (c.*15C>T) in the 3′ UTR was reported in 2 nuclear families each with only a single affected male, precluding proof of cosegregation with disease . The present study has documented cosegregation of the c.*15C>T GJB1 mutation in 4 branches of a large family, with confirmation by linkage analysis.…”
Section: Discussionsupporting
confidence: 51%
“…Given the X‐linked inheritance pattern in the pedigree, GJB1 was analyzed by commercial laboratories on 2 separate occasions but no mutation was identified. With the report of GJB1 *15C>T, we reevaluated the available exome sequence of affected subject VII‐8 and found this variant …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It should be noted however that previous searches for such antibodies in MS have been negative 47. Finally, based on recent studies suggesting that GJB1 promoter mutations may be a more common cause of CMTX than previously suspected, this study is limited by the absence of promoter screening 48. Notwithstanding the above limitations, it remains surprising that the association between CMTX and MS has not been previously noted in reports of larger cohorts of patients with CMTX 49.…”
Section: Discussionmentioning
confidence: 93%
“…Gene dysregulation through aberrant transcriptional regulation is not unprecedented as a disease mechanism in IPN as point mutations have previously been reported in noncoding regulatory sequences (Tomaselli et al, 2017). Point mutations in the 5 0 untranslated region (UTR), 3 0 UTR (Ionasescu, Searby, Ionasescu, Neuhaus, & Werner, 1996) and the neural-specific promoter (P2) sequences of the GJB1 gene (Houlden et al, 2004) have been reported to cause CMTX1.…”
Section: Disruption To Transcriptional Regulationmentioning
confidence: 99%